2021
DOI: 10.1371/journal.pone.0259682
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of massive bleeding in pancreatic surgery based on preoperative patient characteristics using a decision tree

Abstract: Massive intraoperative blood loss (IBL) negatively influence outcomes after surgery for pancreatic ductal adenocarcinoma (PDAC). However, few data or predictive models are available for the identification of patients with a high risk for massive IBL. This study aimed to build a model for massive IBL prediction using a decision tree algorithm, which is one machine learning method. One hundred and seventy-five patients undergoing curative surgery for resectable PDAC at our facility between January 2007 and Octob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
(14 reference statements)
1
4
0
Order By: Relevance
“…Several lines of evidence have shown an association between increased blood loss and poor outcomes in PDAC surgery (15,16,44). Our previous study also demonstrated those relationships (29). These data suggest that more intraoperative blood loss may negatively influence the prognosis of ANH.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Several lines of evidence have shown an association between increased blood loss and poor outcomes in PDAC surgery (15,16,44). Our previous study also demonstrated those relationships (29). These data suggest that more intraoperative blood loss may negatively influence the prognosis of ANH.…”
Section: Discussionsupporting
confidence: 76%
“…A total of 155 patients undergoing curative pancreatic surgery for resectable PDAC at our facility between January 2007 and May 2018 were included in the study. A portion of the subjects in this study had been included in our previous study ( 18 , 29 ). Resectability status was made based on National Comprehensive Cancer Network guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…[15,16,38] Our previous study also demonstrated those relationships. [29] These data suggest that more intraoperative blood loss may negatively in uence the prognosis of ANH. At the same time, we must be deliberate and critically consider that ANH can potentially cause increased intraoperative blood loss.…”
Section: Discussionmentioning
confidence: 92%
“…A portion of the subjects in this study had been included in our previous study. [18,29] Resectability status was made based on National Comprehensive Cancer Network guidelines. All patients had a con rmed pathologic diagnosis.…”
Section: Patients and Study Designmentioning
confidence: 99%
“…The aim of the decision-tree algorithm of Wakiya et al [69] was to identify risk factors leading to massive intraoperative blood loss and consecutively to inferior postoperative outcomes after surgery for PDAC. The AI algorithm generated 14 predictive variables based on preoperative patient characteristics with the best predictors being the type of surgical procedure (open vs MIPS), portal vein resection as well as elevated liver function tests, presence of obstructive jaundice and preoperative biliary drainage.…”
Section: Prediction Of Complicationsmentioning
confidence: 99%